Bamboo as a Sustainable Structural Material: A Comparative Life Cycle Assessment for Green Building Applications - Lhamu, Genden (Journal of Progress in Civil Engineering, 2026)
Bamboo, a fast - growing and versatile natural resource, is increasingly recognized for its role in sustainable construction due to its environmental, economic, and social benefits. After studying various research papers on this topic, I found that bamboo's high tensile strength and flexibility make it an excellent alternative to traditional materials like steel and concrete. Its rapid growth rate, low carbon footprint, and carbon sequestration capabilities further enhance its sustainability. Research also highlights bamboo's natural pest resistance, reducing the need for chemical treatments and improving indoor air quality. Innovative technologies, such as engineered bamboo and hybrid composites, expand its applications in modern architecture. Additionally, studies show that bamboo cultivation supports rural economies by creating sustainable livelihoods. Through case studies, this paper demonstrates bamboo's potential to address global challenges like climate change and resource depletion. The findings advocate for greater adoption of bamboo in green construction, supported by policy frameworks and technological advancements, to create a more sustainable and resilient built environment.